Implementasi PMK Nomor 186/PMK.03/2022 dalam Penghitungan Kembali Pajak Masukan pada PT. X Pasuruan Tahun 2025 - Dewi Nofita Sari; Khojanah Hasan; Dwi Anggarani; Indah Dewi Nurhayati (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
A Taxable Enterprice (Pengusaha Kena Pajak/PKP) that carries out supplies subject to Value Added Tax (VAT) as well as supplies granted VAT exemption facilities faces challenges in detemining the amount of input VAT that can be credited in accordance with tax regulations. This condition requires a recalculation of input VAT as stipulated in Minister of Finance Regulation Number 186/PMK.03/2022, so that tax crediting is carried out accurately and in line with the characteristics of the company’s transactions. This study aims to examine how the recalculation of previously credited input VAT is carried out in accordance with PMK Number 186/PMK.03/2022, and how this affects the company’s profit and loss for 2025. The study employs a qualitative approach with a case study design, involving three informants directly involved in the company’s tax management. Data were abtained throught observation, interview, and documnetation. The results show that PT. X prefers to separate input VAT directly based on this actual use, rather than applying the propotional crediting guidline and the separation of shared costs, as this method is considered more suitable to the company’s operational conditions. Input VAT that cannot be credited is chaged as an expense, thereby reducing the reported profit. These findings underscore the need for a more structured tax invoice classification system, so that input VAT crediting can be carried out more accurately.